Hierarchical lead grid for highly stable oxygen evolution in acidic water at high temperature - Xue, Fengjuan; Kang, Shuai; Dai, Yujie; Li, Tinghua; Shen, Pei Kang; Zhu, Jinliang; Lu, Shun; Fu, Xie; Wang, Liang; Feng, Shuanglong; Sun, Hai; Xue, Zhenhong; et al. (Journal of power sources, 2021)
Developing low cost and high performance catalyst for oxygen evolution reaction is the key to evolving sustainable energy. We synthesize a well-designed architecture comprising of lead grid wrapping by perpendicularly grown lead oxide flakes. Oxygen evolution activities are largely improved after carving the lead foil into lead grid and further enhanced by a secondary structure of lead oxide flakes, with a negatively-shift of onset potential (~65 mV) and smaller overpotential to deliver a current density of 80 mA cm−2 (~350 mV). The electrode is demonstrated to be highly stable under acidic water at 60 °C for 8 h. We believe the excellence in electrochemistry is attributed to increased active sites, good electrical conductivity and sufficient porosity to facilitate reactant water flow and high gas permeability especially at high current densities. [Display omitted] •Electrode in this work is combined of laser cutting and hydrothermal technology.•OER of lead foils are improved after gridding and covering lead oxide flakes.•The lead oxide/lead grid electrode is highly stable under acidic water at 60 °C.•Positive effects are due to increased active sites, good conductivity and porosity.